A Study on the Job Satisfaction of Primary School Teachers in Purasaiwakkam Area, Chennai - Mohana Sasi Kumar; Dr. P. Balasubramani (International Journal of Engineering and Management Research, 2019)
The education is the primary backbone for the development of any nation in the world. It is a powerful tool which is basis for everything in the society. For provide education to all, the schools and its teacher’s plays important role in building the nation. In view of this context, the satisfied teachers in the school can give better education to students rather than dissatisfied teachers. By viewing this as the research focus, this article focuses on the study on the importance of teachers' job satisfaction, It is required to understand the overall teachers' work attitude and work behavior. The paper reviews several factors to ascertain the factors influencing job satisfaction of teacher. The study uses both primary and secondary data. The secondary data were collected various journals and websites. The Primary data were collected by making use of structured questionnaires. The 30 primary school teachers from Helan Sathya Primary School, CSI Primary School and Government Primary School were chosen by convenience sampling method for the study. The questionnaire containing 25 questions with six attributes each. The questionnaire begins with five questions about socio demographic status following with 20 questions with four dimensions namely Career, Colleagues, School and Livelihood. Simple percentage analysis is used to analysis the data. The study finding concludes physical Working Condition, Student interaction, Students IQ, Student Curiosity, Eagerness to learn are some of the concerns of a teacher in teaching. Recognition for Extra Work, clearly defined promotion policies and Salary held a teacher work according to the philosophy/vision/mission/strategy of the management, Teachers works are at times are Challenging & Interesting but on the whole when the management takes of the teachers better, the children are taken care of better. It is suggested that a study can be done among higher secondary school teachers and college teachers.